Persepsi Kesenjangan Sosial Generasi Z: Antara Pilihan Bekerja dan Melanjutkan Pendidikan Tinggi dalam Konteks Budaya - Khairul Akmal; Sinta Maharani; Najwa Maulida Zahra; Ahmad Nurfajri Subhi; Arif Saefudin (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
Social inequality remains a persistent issue shaping the future of younger generations, particularly Generation Z, whose decisions to either pursue higher education or enter the workforce reflect broader cultural, social, and economic dynamics. This study aims to analyze Generation Z’s perceptions of social inequality in relation to their career and educational choices, emphasizing the influence of cultural values and family norms. Using a qualitative approach with thematic analysis, data were collected through interviews with six Generation Z participants aged 17‒28 who had recently decided between working and continuing their education. The findings reveal that Generation Z perceives the difference between working and studying not as a hierarchical gap but as a variation in life choices shaped by access to opportunity, cultural expectations, and individual values. Cultural norms and family influence remain significant but are increasingly balanced with ideals of independence and practicality. Generation Z demonstrates a reflective and adaptive understanding of social mobility, valuing both academic and experiential capital as pathways to success. The study concludes that social inequality among Generation Z is viewed more as unequal access rather than differences in social status. These insights provide implications for education policymakers and institutions to design culturally responsive and flexible programs that integrate work and study opportunities, fostering equality in access and recognition of diverse life choices